TARI RANGGUK KOTA SUNGAI PENUH DALAM KARYA SENI GRAFIS - Wawan Pebriandi; Irwan Irwan (Universitas Negeri Padang, 2021)
Today, the Rangguk Kota Sungai Penuh dance was no longer developed in the current generation because it was often neglected and there was no attention to dance that has long been born in society. The creation of this final work aims to visualized the expression related to the Kota Sungai Penuh rangguk dance in a graphic art work, presenting the rangguk dance movement which was still traditional and still exists today. The method in creating this work used the relief print technique, namely the wood cut type with the reduction print coloring technique and the work process used in the creation of this graphic art work through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) ) Concept Realization, (5) Completion.The results of the visualization of the Kota Sungai Penuh rangguk dance in this graphic art work were in the form of 10 works with the titles: (1) shingles fell, (2) sitting sympathetically, (3) respect, (4) virtuous, (5) meet, (6) facing bamboo, (7) basil flower, (8) apologize, (9) merges, (10) array of fingers.Kata kunci: tari rangguk, tradisional, seni grafis.